Comparison distortion in the mandible skull using panoramic digital radiograpy and Cone Beam Computed Tomography - Manja, Cek Dara (Padjadjaran Journal of Dentistry, 2016)
Panoramic radiography is widely used as a tool supporting the diagnosis in dental practice. Currently the technology has evolved with the presence of radiographic imaging such as Cone Beam Computed Tomography (CBCT) that displays a three-dimensional picture. The purpose of this study was to determine large distortions that occur several regio in the mandible using digital panoramic radiographs and CBCT. Method experimental The research on one of the skull laboratories fitted staples vertically and horizontally in alveolar regions 31, 33, 35, 37, 41, 43, 45, 47, and then measured the length of the staples using the term digital. Furthermore, digital panoramic radiography performed with position 00, +50, +100, -50, -100 and CBCT radiography with 00 positions. Measurement description of radiopaque vertical and horizontal lines on digital panoramic radiographs and CBCT are computerized using the EZ software measurement menu. Calculating percentage distortion radiopaque overview of vertical and horizontal lines on digital panoramic radiographs and CBCT of the mandible by doing a comparison of the actual size of the skull. The results obtained on the percentage of minimal distortion of digital panoramic radiographs vertically was in the 31 region positioned +50at 0,23%, in the 33 region positioned 00at 5,99%, in the 35 region positioned -100at -6,33%, in the 37 region positioned +100at -1,46%, in the 41 region positioned -50at 0,46%, in the 43 region positioned 00at 0,52%, in the 45 region positioned +100at -0,45%, in the 47 region positioned +100at -4,76%. The percentage of minimal distortion of digital panoramic radiographs horizontally all of region was positioned 00. The percentage of minimal distortion of  CBCT all of region was positioned 00 and different on each mandible alveolar region. The conclusion of this study is average distortion that occurs in the mandible using CBCT is more less than digital panoramic radiographs. That is mean CBCT more accurate than digital panoramic radiographs.